Effects of tillage methods and mulching on erosion and physical properties of a sandy clay loam in an equatorial warm humid region - Khatibu, A.I.; Lal, R.; Jana, R.K. (1984)
Field experiments were conducted at Kizimbani Experiment Station in Zanzibar to study the effects of different mulch materials on soil temperature and moisture regimes, soil physical properties, and runoff and soil erosion. A wide range of surface treatments was selected to create diverse conditions of hydro-thermal regime and soil exposure. Treatments consisted of black and white polythene mulch, no-tillage, ridged seedbed, and plowed and harrowed soil surface. For maize and cowpea all mulch and no-till treatments had a greater moisture reserve than other treatments. The maximum soil temperature at a depth of 5 cm was also as much as 6°C lower in the no-tillage than in the other treatments and correlated significantly with solar radiation, soil moisture at depths of 15 and 30 cm, and leaf area index. The infiltration rate declined as a result of two seasons of cultivation and was the least for ridged and the highest for no-till treatments. Runoff was 10.2% in 3.6% and nutrient loss 6.6% of the losses from the bare plot. In the Vuli season, a cool rainy season from September to December, white polythene mulch produced significantly more grain yield of maize, cowpea, and soybean than other treatments. Results of crop performance for the no-till treatment and of rainfall erosivity index are not in agreement with those previously experienced in West Africa.